Natural regeneration of severely degraded terrestrial arid ecosystems needs more than just removing the cause of degradation - Louhaichi, Mounir; Gamoun, Mouldi; AL Hashash, Nouf; Al-Ameer, Fatima; ALRashedi, Dala; Redha, Amal; Alkandari, Fatemah; Niane, Abdoul Aziz (International Center for Agricultural Research in the Dry Areas, 2023)
The study focused on the extensive rangelands in Kuwait, covering more than 75% of the total land area. These rangelands face severe degradation due to factors such as overgrazing, anthropic misuse, and mismanagement. The research aimed to assess the impact of natural restoration, specifically through resting, on vegetation cover and species richness in a fenced 1 km² area. The findings indicated that while perennial species cover remained consistent between fenced and unfenced areas, there was a notable increase in annual species cover within the fenced sections. However, the dominance of the invasive species Stipa capensis showed no significant difference between the two. The study identified a disturbance index of 100%, highlighting the prevalence of therophytes and signaling an ecological imbalance and desertification due to high anthropogenic pressure. The conclusion emphasized the limitations of natural restoration alone in such severely degraded ecosystems, proposing the reintroduction of native species to restore the ecosystem, support the growth of annual palatable species, and enhance overall flora diversity.